A CO2‐Masked Carbene Functionalized Covalent Organic Framework for Highly Efficient Carbon Dioxide Conversion. (21st July 2022) - He, Chang; Si, Duan‐Hui; Huang, Yuan‐Biao; Cao, Rong
Abstract: Free N‐heterocyclic carbenes (NHCs) are generally prepared by treatment of imidazolium precursors with strong alkali reagents, which usually produces inactive NHC dimers. This treatment would destroy porous supports and thus make supported NHC catalysts difficult to recovery and reuse. Herein, we report the first stable CO2 ‐masked N‐heterocyclic carbenes (NHCs) grafted on a porous crystalline covalent organic framework (COF). The stable NHC‐CO2 moieties in the COF‐NHC‐CO2 could be transformed in situ into isolated NHCs by heating, which exhibit superior catalytic performances in hydrosilylation and N‐formylation reactions with CO2 . The NHC sites can reversibly form NHC‐CO2 and thus can be easily recycled and reused while maintaining excellent catalytic activity. Density functional theory calculations revealed that NHC sites can be fully exposed after removal of CO2 ‐masks and rapidly react with silanes, which endows COF‐NHC with high catalytic activity. Abstract : A stable CO2 ‐masked N‐heterocyclic carbene (NHC) decorated covalent organic framework (COF‐NHC‐CO2 ) heterogeneous catalyst is prepared. COF‐NHC‐CO2 catalyzes the hydrosilylation of CO2 and the N‐formylation of amines with CO2 to produce methanol and formamides. The activities rank COF‐NHC‐CO2 among the most active heterogeneous catalysts for these CO2 fixation reactions.